Christmas reunion in Paris - Fielding, Liz (Christmas at the Harrington Park Hotel., 2020)
"Celebrity chef James Harrington never expected to find himself face-to-face with Chloe, his first love, again... Especially with her working as a chambermaid at his luxury hotel! Their chemistry's as strong as ever, but it's clear she's hiding a secret. This Christmas, can James convince Chloe that their love is worth taking a chance on--again?"--